Vibration energy harvesting using macro-fiber composites - Yang, Yaowen (2014)
The decreasing energy consumption of today's portable electronics has invoked the possibility of energy harvesting from the ambient environment for self-power supply. One common and simple method for vibration energy harvesting is to utilize the direct piezoelectric effect. Compared to traditional piezoelectric materials such as lead zirconate titanate (PZT), macro-fiber composites (MFC) are characterized by their flexibility on large deformation. However, the energy generated by MFC is still far smaller than that required by electronics at present. In this paper, a vibration energy harvesting system prototype with MFC patches bonded to a cantilever beam is fabricated and tested. A finite element analysis (FEA) model is established to estimate the output voltage of the MFC harvester. The energy accumulation procedure in the capacitor is simulated by using the electronic design automation (EDA) software. The simulation results are validated by the experimental ones. Finally, to optimize the efficiency of energy harvesting, the effects of the electrical properties of MFC as well as the geometric configurations of the cantilever beam and MFC are parametrically studied by combining the FEA and EDA simulations.